2021
DOI: 10.4103/jpbs.jpbs_755_20
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Impression Materials with Glutaraldehyde, Ultraviolet Radiation, and Autoclave: A Comparative Study

Abstract: Background: The present study was conducted to compare various methods of disinfection of impression materials such as glutaraldehyde, ultraviolet (UV) radiation, and autoclave. Materials and Methods: The present study was conducted on eighty alginate impression materials which were disinfectant with 2.2% glutaraldehyde, UV radiation, and autoclave. The pre- and postbacterial count was assessed. Results: The mean premicrobial contamination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…However, due to the fact that this study was conducted using impressions taken from the patients, there was no detailed information on the specific microbial strains present in the samples [ 16 ]. Another study demonstrated lower UV radiation effectiveness than autoclave, used for the elimination of pathogenic microorganisms from alginate impressions [ 17 ]. Godbole et al revealed a lack of a significant negative influence of UV light disinfection on the dimensional stability of polyvinyl siloxane impressions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the fact that this study was conducted using impressions taken from the patients, there was no detailed information on the specific microbial strains present in the samples [ 16 ]. Another study demonstrated lower UV radiation effectiveness than autoclave, used for the elimination of pathogenic microorganisms from alginate impressions [ 17 ]. Godbole et al revealed a lack of a significant negative influence of UV light disinfection on the dimensional stability of polyvinyl siloxane impressions.…”
Section: Discussionmentioning
confidence: 99%
“…It must be taken into account that various disinfectants also pose a risk of alterations of dimensions and surface chemistry (e.g., wettability) of dental impressions. To avoid the negative influence of these chemical agents on different material properties of dental impressions, researchers are looking for other methods of disinfection, such as gaseous ozone [ 13 ], microwave irradiation [ 14 , 15 ], ultraviolet radiation [ 16 , 17 , 18 ], or electrolyzed oxidizing water [ 19 , 20 ]. Such alternative techniques may be particularly beneficial to oral health maintenance when applied to the most basic impression material used nowadays, based on sodium alginate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using UV light tubes with higher wattage has been found to significantly reduce colony counts in a shorter time. The most effective antibacterial efficiency through UV light exposure occurs at 24 watts (3750 µw/cm2), and higher wattages result in a faster reduction in C. albicans colony counts, ultimately reaching zero [8,14]. Samra et al (2018) proposed that the ultraviolet method is a favorable choice for disinfecting impressions without compromising their dimensional stability [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dentists and dental staff must be familiar with standardized procedures for disinfecting dental impressions and casts. The literature describes various methods of impression disinfection, including chemical disinfection, microwave treatment, autoclaving, and ultraviolet radiation, each with its advantages, disadvantages, and effects on impression materials and casts [ 8 , 9 ]. Recently, impression materials have been directly integrated with antimicrobials and nanoparticles, enabling the material to possess self-disinfecting properties.…”
Section: Introductionmentioning
confidence: 99%